Prevalences of Gastrointestinal Parasitic in Dogs and Cats at Kaki 4 and K-5 Clinics Kediri City - Taufan Ary Handoko; Poedji Hastoetik; Mufasirin Mufasirin; Herry Agoes Hermadi; Nusdianto Triakoso (Universitas Airlangga, 2022)
Parasitic diseases of the gastrointestinal have a bad impact for dogs and cats. This study was conducted to determine the prevalence, types, and different of maintenance system on dogs and cats in Kaki 4 and K-5 clinics Kediri city. This study used 100 samples of cat and dog feses. The result showed 4% prevalence i.e. 2 samples are positively infected by Ancylostoma sp. (2%), 1 sample is positively infected by Toxocara cati (1%), and 1 sample is positively infected by Ancylostoma sp., Dipylidium caninum, and Toxascaris leonina (1%). Classified by maintenance system, the dogs and cats that maintenance with semi-intensif system prevalence was 2.1% (2/96), while intensif prevalence of 50% (2/4). Based on gender, male prevalence of 7.4% (4/54), while a female was not infected by gastrointestinal parasite. Classified by age, the dogs and cats under age of one year the prevalence of 4.2% (2/47), while those age one year or more prevalence was 3.8% (2/53). Based antiparasitic drugs that given the dogs and cats prevalence was 2.1% (2/96), while not given prevalence of 50% (2/4). Based on breed, the pure breed prevalence of 2.8% (1/36), mix breed prevalence of 12.5% (1/8), while the domestic breed prevalence was 3.6% (2/56).